An efficient process for recovering copper as CuO nanoparticles from acidic waste etchant via chemical precipitation and thermal decomposition: Turning waste into value-added product. (1st October 2022) - Che, Jianyong; Zhang, Wenjuan; Ma, Baozhong; Wang, Chengyan
Abstract: A succinct process for recovering Cu from acidic waste etchant (AWE) was developed in this work, which included recycling Cu via oxalate precipitation, preparing CuO nanoparticles by thermal decomposing the precipitate, and recovering NaCl via evaporation crystallization. A comparison of copper precipitation by H2 C2 O4 and Na2 C2 O4 suggested that an efficient recovery efficiency of Cu was obtained by Na2 C2 O4 (∼99%), which was higher than that by H2 C2 O4 (80.31%). Through thermodynamic analysis, a H + -release mechanism was proposed to explain the significant difference in copper precipitation between Na2 C2 O4 and H2 C2 O4 . By parameter optimization, 99.8% of Cu was recovered without adjusting pH value under optimal conditions, such as temperature of 40 °C, sodium oxalate of 1.2 mol/mol, and reaction time of 2 h. Furthermore, CuO nanoparticles with a purity of 99.92% and particle size of 30 nm were prepared, and the phase transformation of Cu was investigated in-depth using X-ray diffraction (XRD), Scanning electron microscope (SEM), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectrum (FT-IR). Finally, the chloride ions were recovered as NaCl at 99.51% purity. This study provides a potential route to deal with strongly acidic waste etchant and achieve its high-value utilization. Graphical abstract: Image 1 Highlights: An efficient process for recycling copper from acidic waste etchant was proposed. Na2 C2 O4 presented a better performance in copper precipitation than H2 C2 O4 . A thermodynamic mechanism of copper precipitation by oxalate was understood. 99.8% of copper was precipitated by Na2 C2 O4 without adjusting pH. High value-added CuO nanoparticles were obtained with a purity of 99.92%.